Pemberdayaan dan Peningkatan Perilaku Cuci Tangan Pakai Sabun (CTPS) Dalam Pencegahan Penyebaran Covid-19 di Kelurahan Dorpedu Kota Ternate Provinsi Maluku Utara - Purnama Sidebang (Jurnal Pengabdian UNDIKMA, 2021)
The purpose of this community service is to increase the knowledge and competence of the community, especially housewives in clean and healthy living behavior, namely about washing hands with soap, so as to prevent the transmission of the Covid-19 disease. The method used in this service is counseling and community empowerment. The procedure for implementing this activity begins with a pretest, counseling, demonstration, mentoring, distribution of pocket books and leaflets and ends with a posttest. The results of this service activity show that there is an increase in the knowledge of the Dorpedu Village community regarding the implementation of CTPS, important times for the implementation of CTPS and the community is motivated to be consistent in implementing it, besides that facilities for washing hands with soap are already available as an effort to prevent the transmission of Covid-19 . Overall, the group of housewives was enthusiastic in participating in each of these service activities.